Alternative translation initiation codons for the plastid maturase MatK: unraveling the pseudogene misconception in the Orchidaceae. (December 2015) - Barthet, Michelle; Moukarzel, Keenan; Smith, Kayla; Patel, Jaimin; Hilu, Khidir
Abstract Background The plastid maturase MatK has been implicated as a possible model for the evolutionary "missing link" between prokaryotic and eukaryotic splicing machinery. This evolutionary implication has sparked investigations concerning the function of this unusual maturase. Intron targets of MatK activity suggest that this is an essential enzyme for plastid function. ThematK gene, however, is described as a pseudogene in many photosynthetic orchid species due to presence of premature stop codons in translations, and its high rate of nucleotide and amino acid substitution. Results Sequence analysis of thematK gene from orchids identified an out-of-frame alternative AUG initiation codon upstream from the consensus initiation codon used for translation in other angiosperms. We demonstrate translation from the alternative initiation codon generates a conserved MatK reading frame. We confirm that MatK protein is expressed and functions in sample orchids currently described as having amatK pseudogene using immunodetection and reverse-transcription methods. We demonstrate using phylogenetic analysis that this alternative initiation codon emergedde novo within the Orchidaceae, with several reversal events at the basal lineage and deep in orchid history. Conclusion These findings suggest a novel evolutionary shift for expression ofmatK in the Orchidaceae and support the function of MatK as a group II intron maturase in the plastid genome of land plants including the orchids.